Titanium anode film stainless steel composite material surface PVD electrolytic deplating agent and deplating method thereof
By using strong acid and alkali salts, acid salts of polybasic acids, chelating agents and corrosion inhibitors in PVD deplating agents to control pH values, the problem of difficult deplating of titanium anode film stainless steel composite materials in the prior art is solved, and the problem of deplating of titanium anode film stainless steel composite materials is realized. Efficient, safe and environmentally friendly deplating effect.
Patent Information
- Application Number
- CN202411566355.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-03
AI Technical Summary
In the existing PVD deplating methods, chemical methods use strong oxidants to decompose and fail, and the pollution problem is serious. The electrolytic method uses strong acids or strong alkalis to be harmful and wastewater treatment is difficult. In particular, the deplating of titanium anode film stainless steel composite materials is more difficult. In addition, existing electrolytic removal agents are corrosive to stainless steel and anode films, and the removal speed is slow.
Provide a PVD electrolytic deplating agent on the surface of titanium anode film stainless steel composite material, which consists of acid salts including strong acids and alkali salts, polyacids, chelating agents and corrosion inhibitors. The pH value is controlled between 3.0 and 6.0 during the electrolysis process, and the pressure is reduced. The corrosion of stainless steel and anode film is electrolytic deplating under room temperature.
It achieves good deplating effect, fast speed, no toxic and harmful substances, reduces production costs and energy consumption, meets the needs of environmentally friendly and safe production, and is safe and corrosion-free for various metal parts substrates.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytic stripping, and in particular to a PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material and a stripping method thereof. Background Art
[0002] As a rare metal material with light weight, high strength, wear resistance and corrosion resistance, titanium is mainly used in the aerospace field and the chemical field with high corrosion resistance, such as aircraft fuselage components, aircraft engine components, etc., but its high cost limits its large-scale application. Aluminum alloy has the advantages of light weight, good electrical and thermal conductivity, and low price. It has been widely used in aerospace, shipbuilding, transportation and other fields, but its performance deteriorates in high temperature and corrosive environment, and its impact resistance is poor. Titanium-aluminum composite materials can give full play to the advantages of both materials and expand into a high-quality material with light weight, high strength, high wear resistance and high corrosion resistance, while reducing production costs, and have great application prospects. In order to further improve the corrosion resistance of titanium-aluminum composite materials, anodizing is usually performed on the surface of aluminum alloy to obtain titanium anode film composite materials. Titanium anode film composite materials are currently widely used in mobile phone middle frames, while other supporting buttons and charging ports are still made of stainless steel, thus forming titanium anode film stainless steel composite materials.
[0003] PVD coating (physical vapor deposition technology, used to deposit thin films with special functions on the surface of the substrate) is an environmentally friendly vacuum coating process. Due to its excellent wear and corrosion resistance, PVD is often used to give parts better wear resistance, corrosion resistance, hardness and gorgeous decorative effects. The PVD coating process is common in industrial, non-industrial and cosmetic applications. In modern manufacturing, PVD is a very important surface treatment process. Due to the complexity of PVD coating technology, defective products are inevitable in the production process, so the defective products must be deplated. There are two main PVD stripping methods: chemical and electrolytic. The chemical method usually uses strong oxidants such as potassium permanganate or hydrochloric acid for stripping. Among them, strong oxidants are easy to decompose and become ineffective, have a short shelf life, and potassium permanganate has extremely high chroma and high wastewater treatment costs. Hydrochloric acid is extremely volatile, causing surrounding air pollution. If the highly corrosive chloride ions are not cleaned properly and brought into the chrome plating solution, it will cause chrome plating solution failure. The electrolytic method usually uses strong acids (nitric acid, sulfuric acid, hydrochloric acid, etc.), strong alkalis (sodium hydroxide, potassium hydroxide, etc.), nitrates, and cyanides for stripping, which are not only toxic and harmful, and highly corrosive, but also difficult to treat the wastewater generated, and the treatment cost is high.
[0004] PVD stripping of titanium anode film stainless steel composite materials is more difficult. The existing chemical stripping method containing strong oxidants is highly corrosive to the anode film; and among the electrolytic stripping agents, acidic agents are prone to corrode stainless steel during the electrolysis process due to the depolarization phenomenon of hydrogen ions, and alkaline agents have the problem of corroding the anode film and slow stripping speed.
[0005] In order to meet the needs of environmentally friendly and safe production, and to improve the effect and efficiency of stripping while ensuring the safety of the substrate, it is urgent to find a better PVD electrolytic stripping agent on the surface of titanium anode film stainless steel composite materials to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to provide a PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material in view of the deficiencies in the prior art, which has good stripping effect and fast stripping speed and does not contain strong acids, strong alkalis, nitrates, cyanides, hexamethylenetetramine, halogens and other reagents.
[0007] The technical solution adopted by the present invention is as follows:
[0008] According to one aspect of the present invention, a PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material is provided, which is composed of the following components in percentage by mass: 5-10% of strong acid and strong alkali salts, 8-15% of acid salts of polyacids, 2-5% of chelating agents, 3-7% of corrosion inhibitors, and the balance is water.
[0009] Furthermore, the strong acid and strong base salt is at least one of sodium sulfate and potassium sulfate; the strong acid and strong base salt is dissolved in water, which can provide conductive ions, reduce the resistance of the liquid, and reduce energy consumption;
[0010] Furthermore, the acid salt of the polyacid is at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, monosodium succinate, monosodium citrate, potassium dihydrogen citrate, disodium hydroxyethylidene diphosphonate, and dipotassium hydroxyethylidene diphosphonate; the acid salt of the polyacid is used to provide hydrogen ions in the solution and control the concentration of hydrogen ions in the liquid, thereby controlling the electrolytic reaction rate of the chromium-containing plating layer, and greatly reducing the corrosion of the reagent to the stainless steel and the anode film during electrolysis compared to the strong acid system;
[0011] Furthermore, the chelating agent is at least one of sodium hexametaphosphate, sodium citrate, sodium gluconate, sodium alginate, and sodium polyacrylate. The chelating agent is used to chelate the chromium ions stripped from the surface of the substrate, prevent the formation of insoluble matter on the surface of the coating, and inhibit anode polarization;
[0012] Furthermore, the corrosion inhibitor is at least one of thiourea and urea; the corrosion inhibitor is used to protect stainless steel and the anode film substrate.
[0013] Furthermore, the pH of the electrolytic stripping agent stock solution is 3.0 to 6.0.
[0014] At room temperature, the components in the above mass percentages can be mixed to obtain the PVD electrolytic stripping agent on the surface of the titanium anode film stainless steel composite material provided by the present invention.
[0015] Another aspect of the present invention provides a method for using a PVD electrolytic stripping agent on the surface of a titanium anode film stainless steel composite material, the steps of which include:
[0016] (1) taking the above-prepared PVD electrolytic stripping agent stock solution on the surface of the titanium anode film stainless steel composite material, adding it into an electrolytic cell, and adding a workpiece to be stripped into the electrolytic cell;
[0017] (2) The workpiece to be deplated is used as the anode and the stainless steel plate / lead plate is used as the cathode. The workpiece is placed in an electrolytic deplating solution for electrolytic deplating until the coating is completely deplated. When the deplating solution in the electrolytic tank is reduced as the workpiece is taken away, the original solution can be directly added.
[0018] In step (2), the voltage of the electrolysis may be 8 to 16 V;
[0019] In step (2), the electrolysis time is 3-15 min;
[0020] In step (2), the electrolysis temperature is room temperature.
[0021] The principle of the invention is as follows: strong acid and strong alkali salts are dissolved in water to provide conductive ions, reduce the resistance of the liquid and reduce energy consumption; the acid salt of the polyacid is used to provide hydrogen ions in the solution and has buffering performance to control the concentration of hydrogen ions in the liquid, so that the pH value of the solution is maintained at 3.0-6.0, which plays a role in controlling the electrolytic reaction rate of the chromium-containing plating layer and the corrosion of the reagent to the substrate, and greatly reduces the corrosion of the reagent to stainless steel and the anode film during electrolysis compared with the strong acid and strong alkali system; the chelating agent is used to chelate the chromium ions stripped from the surface of the substrate, avoid the formation of insoluble substances on the surface of the plating layer, and inhibit the polarization of the anode; the corrosion inhibitor is used to protect the stainless steel and the anode film substrate.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] (1) The present invention adopts a highly efficient compound of strong acid and strong base salts, acid salts of polyacids, chelating agents, corrosion inhibitors and water, which has an excellent stripping effect on PVD film layers, and the coating is stripped cleanly and thoroughly, and is safe and non-corrosive to various metal component substrates. The stripping time is short and the service life is long. The stripping can be completed at a relatively low electrolysis voltage, and the stripping agent can be used at room temperature without heating. It not only significantly improves the stripping production efficiency, but also reduces energy consumption and greatly reduces the production cost.
[0024] (2) The electrolytic stripping agent of the present invention does not contain toxic, harmful, and highly corrosive substances such as strong acids, strong bases, nitrates, cyanides, hexamethylenetetramine, and halogens, thus meeting the needs of environmentally friendly and safe production. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0026] The embodiment of the present invention provides a PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material, which is composed of the following components in percentage by mass: 5-10% of strong acid and strong alkali salts, 8-15% of acid salts of polyacids, 2-5% of chelating agents, 3-7% of corrosion inhibitors, and the remainder is water.
[0027] Furthermore, the strong acid and strong base salt includes at least one of sodium sulfate and potassium sulfate;
[0028] Furthermore, the acid salt of the polyacid includes at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, monosodium succinate, monosodium citrate, potassium dihydrogen citrate, disodium hydroxyethylidene diphosphonate, and dipotassium hydroxyethylidene diphosphonate;
[0029] Furthermore, the chelating agent includes at least one of sodium hexametaphosphate, sodium citrate, sodium gluconate, sodium alginate, and sodium polyacrylate.
[0030] Furthermore, the corrosion inhibitor includes at least one of thiourea and urea.
[0031] Furthermore, the pH of the electrolytic stripping agent stock solution is 3.0 to 6.0.
[0032] At room temperature, the above mass percentage combinations are mixed to obtain the PVD electrolytic stripping agent on the surface of the titanium anode film stainless steel composite material of the present invention.
[0033] The present invention provides
[0034] In order to further illustrate the present invention, the technical solution provided by the present invention is described in detail below in conjunction with embodiments.
[0035] Example 1
[0036] A PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material is composed of the following components in percentage by mass: 7% sodium sulfate, 12% potassium dihydrogen phosphate, 2% sodium alginate, 3% thiourea, and the balance water.
[0037] The above components are mixed to obtain an electrolytic stripping agent. The workpiece to be stripped is used as the anode and the stainless steel plate is used as the cathode, and placed in the above electrolytic stripping agent. Under room temperature conditions, the electrolytic voltage is set to 8V, and the electrolytic stripping is performed for 8 minutes. The coating is completely stripped and the substrate is not corroded.
[0038] Example 2
[0039] A PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material is composed of the following components in percentage by mass: 10% potassium sulfate, 13% potassium dihydrogen citrate, 4% sodium gluconate, 5% thiourea, and the balance water.
[0040] The above components are mixed to obtain an electrolytic stripping agent. The workpiece to be stripped is used as the anode and the stainless steel plate is used as the cathode, and placed in the above electrolytic stripping agent. Under room temperature conditions, the electrolytic voltage is set to 12V, and the electrolytic stripping is performed for 5 minutes. The coating is completely stripped and the substrate is not corroded.
[0041] Example 3
[0042] A PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material is composed of the following components in percentage by mass: 7% sodium sulfate, 8% dipotassium hydroxyethylidene diphosphonate, 5% sodium polyacrylate, 6% urea, and the balance water.
[0043] The above components are mixed to obtain an electrolytic stripping agent. The workpiece to be stripped is used as the anode and the stainless steel plate is used as the cathode, and placed in the above electrolytic stripping agent. Under room temperature conditions, the electrolytic voltage is set to 8V, and the electrolytic stripping is performed for 12 minutes. The coating is completely stripped and the substrate is not corroded.
[0044] Example 4
[0045] A PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material is composed of the following components in percentage by mass: 5% sodium sulfate, 15% dipotassium hydroxyethylidene diphosphonate, 5% sodium hexametaphosphate, 7% urea, and the balance water.
[0046] The above components are mixed to obtain an electrolytic stripping agent. The workpiece to be stripped is used as the anode and the stainless steel plate is used as the cathode, and placed in the above electrolytic stripping agent. Under room temperature conditions, the electrolytic voltage is set to 14V, and the electrolytic stripping is performed for 3 minutes. The coating is completely stripped and the substrate is not corroded.
[0047] Comparative Example 1
[0048] A PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material is composed of the following components in percentage by mass: 5% sodium sulfate, 5% dipotassium hydroxyethylidene diphosphonate, 5% sodium hexametaphosphate, 7% urea, and the balance water.
[0049] The above components are mixed to obtain an electrolytic stripping agent. The workpiece to be stripped is used as the anode and the stainless steel plate is used as the cathode. The workpiece is placed in the above electrolytic stripping agent. Under room temperature conditions, the electrolytic voltage is set to 14V. The electrolytic stripping is performed for 20 minutes. There is a lot of residual coating. The electrolytic stripping is performed for 45 minutes. The coating is completely stripped and the substrate is not corroded.
[0050] Comparative Example 2
[0051] A PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material is composed of the following components in percentage by mass: 5% sodium sulfate, 5% sulfuric acid, 5% sodium hexametaphosphate, 7% urea, and the balance water.
[0052] The above components are mixed to obtain an electrolytic stripping agent. The workpiece to be stripped is used as the anode and the stainless steel plate is used as the cathode. The workpiece is placed in the above electrolytic stripping agent. Under room temperature conditions, the electrolytic voltage is set to 8V. The electrolytic stripping is performed for 10 minutes. The coating is completely stripped. The stainless steel and the anode film are severely corroded. The stainless steel becomes matte and has pits. The anode film is fogged and partially dissolved.
[0053] Comparative Example 3
[0054] A PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material is composed of the following components in percentage by mass: 7% sodium sulfate, 12% potassium dihydrogen phosphate, 2% sodium alginate, and the balance water.
[0055] The above components are mixed to obtain an electrolytic stripping agent. The workpiece to be stripped is used as the anode and the stainless steel plate is used as the cathode. The workpiece is placed in the above electrolytic stripping agent. Under room temperature conditions, the electrolytic voltage is set to 8V. The electrolytic stripping is performed for 8 minutes. The coating is completely stripped, and the stainless steel and the anode film are slightly corroded and discolored.
[0056] Comparative Example 4
[0057] A PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material is composed of the following components in percentage by mass: 5% lactic acid, 5% maleic acid, 5% citric acid, 10% tartaric acid, 5% polyvinyl pyrrolidone (weight average molecular weight of 1000-2000), 5% polyvinyl alcohol (weight average molecular weight of 1000-3000), and the balance water.
[0058] The above components are mixed to obtain an electrolytic stripping agent. The workpiece to be stripped is used as the anode and the stainless steel plate is used as the cathode. The workpiece is placed in the above electrolytic stripping agent. Under room temperature conditions, the electrolytic voltage is set to 15V. The electrolytic stripping is performed for 18 minutes. The coating is completely stripped. The stainless steel and the anode film are moderately corroded. The stainless steel is fogged and partially pitted. The anode film is partially fogged.
[0059] Comparative Example 5
[0060] A PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material is composed of the following components in percentage by mass: 5% potassium carbonate, 6% potassium sulfite, 6% sodium gluconate, 2% sodium silicate, 0.5% methyl cellulose (weight average molecular weight is 15000-20000), and the balance water.
[0061] The above components are mixed to obtain an electrolytic stripping agent. The workpiece to be stripped is used as the anode and the stainless steel plate is used as the cathode, and placed in the above electrolytic stripping solution. Under room temperature conditions, the electrolytic current is set to 15V, and the electrolytic stripping is performed for 120 minutes. The coating is not completely stripped, the anode film is severely corroded, fogging and partial dissolution.
[0062] Table 1 shows the electrolytic test results of PVD electrolytic stripping agent on the surface of titanium anode film stainless steel composite material
[0063] Example Stripping time Stripping Substrate corrosion Example 1 8min Net Refund No corrosion Example 2 5min Net Refund No corrosion Example 3 12min Net Refund No corrosion Example 4 3min Net Refund No corrosion Comparative Example 1 45min Net Refund No corrosion Comparative Example 2 10min Net Refund The stainless steel becomes matte and has pits, and the anodic film becomes foggy and partially dissolved Comparative Example 3 8min Net Refund Stainless steel and anodic film have slight corrosion discoloration Comparative Example 4 18min Net Refund Stainless steel is fogged and partially pitted, and the anodic film is partially fogged Comparative Example 5 120min Not refunded The anode film is severely corroded, fogging and partially dissolved
[0064] As can be seen from Table 1, Examples 1 to 4 have good stripping speeds, and are safe and non-corrosive to substrates such as anode films and stainless steel. By comparing the data, it can be seen that, compared with Example 4, Comparative Example 1 reduces the amount of acid salt of the polyacid, and the stripping speed slows down; Comparative Example 2 and Comparative Example 4 are strong acidic formulas with a pH value less than 3.0, and the stripping speed is fast, but there is obvious corrosion to stainless steel and anode films; No corrosion inhibitor is added in Comparative Example 3, and the film layer can be removed, but there is corrosion to stainless steel and anode films; Comparative Example 5 is an alkaline formula system, and the stripping speed is slow and the corrosion to the anode film is serious.
[0065] The PVD electrolytic stripping agent for the surface of the titanium anode film stainless steel composite material of the present invention adopts a highly efficient compound of strong acid and strong alkali salts, acid salts of polyacids, chelating agents, corrosion inhibitors and water, and has a short stripping time, clean and thorough stripping, and can be used at room temperature without heating. At the same time, it is safe for titanium, anode film, and stainless steel substrates, and has a long service life. The electrolytic stripping agent of the present invention does not contain toxic and harmful, highly corrosive substances such as strong acids and strong alkalis, nitrates, cyanides, hexamethylenetetramine, halogens, etc., and meets the needs of environmentally friendly safety production.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A PVD electrolytic stripping agent for the surface of a titanium anode film stainless steel composite material, characterized in that: The invention is composed of the following components in percentage by mass: 5-10% of strong acid and strong alkali salt, 8-15% of acid salt of polyacid, 2-5% of chelating agent, 3-7% of corrosion inhibitor and the balance of water.
2. The PVD electrolytic stripping agent for the surface of the titanium anode film stainless steel composite material according to claim 1, characterized in that: The strong acid and strong base salt is at least one of sodium sulfate and potassium sulfate.
3. The PVD electrolytic stripping agent for the surface of the titanium anode film stainless steel composite material according to claim 1, characterized in that: The acid salt of the polyacid is at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, monosodium succinate, monosodium citrate, potassium dihydrogen citrate, disodium hydroxyethylidene diphosphonate, and dipotassium hydroxyethylidene diphosphonate.
4. The PVD electrolytic stripping agent for the surface of the titanium anode film stainless steel composite material according to claim 1, characterized in that: The chelating agent is at least one of sodium hexametaphosphate, sodium citrate, sodium gluconate, sodium alginate and sodium polyacrylate.
5. The PVD electrolytic stripping agent for the surface of the titanium anode film stainless steel composite material according to claim 1, characterized in that: The corrosion inhibitor is at least one of thiourea and urea.
6. The PVD electrolytic stripping agent for the surface of the titanium anode film stainless steel composite material according to claim 1, characterized in that: The pH value of the electrolytic stripping agent stock solution is 3.0-6.
0.
7. A method for preparing a PVD electrolytic stripping agent on the surface of a titanium anode film stainless steel composite material according to any one of claims 1 to 6, characterized in that: At room temperature, the components in the above mass percentages are mixed to obtain the PVD electrolytic stripping agent on the surface of the titanium anode film stainless steel composite material.
8. A method for using the PVD electrolytic stripping agent on the surface of the titanium anode film stainless steel composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) taking the above-prepared PVD electrolytic stripping agent stock solution on the surface of the titanium anode film stainless steel composite material, adding it into an electrolytic cell, and adding a workpiece to be stripped into the electrolytic cell; (2) The workpiece to be deplated is used as the anode and the stainless steel plate / lead plate is used as the cathode. The workpiece is placed in an electrolytic deplating solution for electrolytic deplating until the coating is completely deplated. When the deplating solution in the electrolytic tank is reduced as the workpiece is taken away, the original solution can be directly added.
9. The method for preparing the PVD electrolytic stripping agent on the surface of the titanium anode film stainless steel composite material according to claim 8, characterized in that: In step (2), the electrolysis voltage may be 8-16V, the electrolysis time may be 3-15min, and the electrolysis temperature may be room temperature.
